2017
DOI: 10.1152/ajpgi.00215.2017
|View full text |Cite|
|
Sign up to set email alerts
|

Enteric serotonin and oxytocin: endogenous regulation of severity in a murine model of necrotizing enterocolitis

Abstract: Necrotizing enterocolitis (NEC), a gastrointestinal inflammatory disease of unknown etiology that may also affect the liver, causes a great deal of morbidity and mortality in premature infants. We tested the hypothesis that signaling molecules, which are endogenous to the bowel, regulate the severity of intestinal and hepatic damage in an established murine NEC model. Specifically, we postulated that mucosal serotonin (5-HT), which is proinflammatory, would exacerbate experimental NEC and that oxytocin (OT), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 89 publications
(96 reference statements)
0
16
1
Order By: Relevance
“…However, the severity of these peaks is different; again, it is unclear whether the lesser injury peak seen in the SERTKO is due to protection from injury or have actually been the subject of recent studies. 20,21 Interestingly, when compared to the results of the current study, it initially appears counterintuitive that knockout of the SERT would result in worsening inflammation in a colitis model and increased severity of disease in a model of necrotizing enterocolitis. An important difference between the current study and the above-mentioned work relates to the end points studied.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…However, the severity of these peaks is different; again, it is unclear whether the lesser injury peak seen in the SERTKO is due to protection from injury or have actually been the subject of recent studies. 20,21 Interestingly, when compared to the results of the current study, it initially appears counterintuitive that knockout of the SERT would result in worsening inflammation in a colitis model and increased severity of disease in a model of necrotizing enterocolitis. An important difference between the current study and the above-mentioned work relates to the end points studied.…”
Section: Discussioncontrasting
confidence: 62%
“…Likewise, could a patient with inflammatory bowel disease be treated with 5‐HT manipulation along with other surgical and medical therapy to decrease the length of resected intestine and aid in post‐operative adaptation? The above questions have actually been the subject of recent studies . Interestingly, when compared to the results of the current study, it initially appears counterintuitive that knockout of the SERT would result in worsening inflammation in a colitis model and increased severity of disease in a model of necrotizing enterocolitis.…”
Section: Discussionmentioning
confidence: 48%
“…Although neuronal‐derived 5‐HT may have anti‐inflammatory effects, decreased mucosal 5‐HT, produced by either knockout of tryptophan hydroxylase I (TPH1), the rate‐limiting enzyme in the biosynthesis of EC cell 5‐HT, or use of a chemical inhibitor of TPH activation, leads to an amelioration of inflammation . Conversely, knockout of SERT, which increases 5‐HT effects by decreasing its reuptake and metabolism, leads to increased NEC inflammation . Although SERT inhibitors (SSRI) are commonly used during pregnancy and lactation, and various behavioral and pulmonary effects on the neonate have been described, only very limited data suggest a link between maternal SSRI use and NEC …”
Section: Implications For Neurogastroenterologymentioning
confidence: 99%
“…22,56,57 Recently, it has been demonstrated that 5-HT regulates inflammation in an experimental murine NEC model. 58 Although neuronal-derived 5-HT may have anti-inflammatory effects, decreased mucosal 5-HT, produced by either knockout of tryptophan hydroxylase I (TPH1), the rate-limiting enzyme in the biosynthesis of EC cell 5-HT, or use of a chemical inhibitor of TPH activation, leads to an amelioration of inflammation. 58 Conversely, knockout of SERT, which increases 5-HT effects by decreasing its reuptake and metabolism, leads to increased NEC inflammation.…”
Section: Impli C Ati On S For Neu Rog a S Troenterologymentioning
confidence: 99%
See 1 more Smart Citation